2007
DOI: 10.1080/10245330601111813
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FLT3 internal tandem duplications on Indian acute promyelocytic leukemia patients: Prognostic implications

Abstract: Despite recent advances in the treatment of acute promyelocytic leukemia (APL), early mortality and relapses still occur. With the view to evaluate the role of FLT3 mutation in APL, 54 patients (median age 28 years, range11-57 years, male to female ratio 1.2:1, median TLC 8.4 x 10(9)/l, range 1-170 x 10(9)/l) were studied by reverse transcriptase-PCR. Forty-two patients (77%) achieved first remission (CR1). Ten (18.5%) of the 54 patients had internal tandem duplication of exons 11 and 12 of the FLT3 gene. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
4
9
0
Order By: Relevance
“…As previously reported, 11,13,14,33 patients with ITD had an increased risk of induction death also in our study. However, the multivariate analysis made clear that this was due to the association with hyperleukocytosis, a wellestablished risk factor for induction death.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As previously reported, 11,13,14,33 patients with ITD had an increased risk of induction death also in our study. However, the multivariate analysis made clear that this was due to the association with hyperleukocytosis, a wellestablished risk factor for induction death.…”
Section: Discussionsupporting
confidence: 77%
“…Activating mutations of FLT3 have been reported in APL at frequencies within the range of 12% to 39% for FLT3-ITD (median 21%), [5][6][7][8][9][10][11][12][13][14][15]17,33,34 and 6% to 22% for FLT3-D835 (median 9%). [6][7][8][9][10][11][12]14,15,17 The incidence of these mutations in our Prognostic value of FLT3 mutations in APL haematologica | 2011; 96 (10)study, 22% and 9%, respectively, are consistent with the reported data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface FLT3 receptor protein (CD135) was studied on intact leukemic blasts using bone marrow or peripheral blood samples, by flow cytometric analysis along with immunophenotypic study as described earlier [17].…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Various study groups including few Indian studies have reported the association of activating mutations of FLT3 ITD, with the poor clinical outcome in AML patients [5,[14][15][16][17][18], with only few studies reporting absence of association of FLT3 ITD with disease prognosis [19,20].…”
Section: Introductionmentioning
confidence: 99%